Perbedaan kecukupan protein dan durasi menstruasi antara remaja putri anemia dan tidak anemia di wilayah kerja Puskesmas Sukapakir, Bandung - Shadiqa Bilqisthi Aulia Nurrahman; Ahdiyatul Fauza; Delita Septia Rosdiana; Syifa F. Syihab (Poltekkes Kemenkes Aceh, 2026)
Background: Anemia remains a public health problem among adolescent girls. Inadequate protein intake may impair hemoglobin synthesis and iron transport, whereas prolonged menstruation may increase blood and iron loss. Evidence comparing these factors between anemic and non-anemic adolescent girls remains limited.Objectives: To compare protein adequacy and menstrual duration between anemic and non-anemic adolescent girls in the Sukapakir Health Center working area, Bandung.Methods: This analytical cross-sectional study was conducted in January–February 2025. Sixty-four female students aged 15–19 years were selected using purposive sampling and divided into anemic (n = 32) and non-anemic (n = 32) groups. Anemia was defined as a hemoglobin level <12 g/dL. Protein intake was assessed using two nonconsecutive 24-hour dietary recalls, and menstrual duration was obtained using a questionnaire. Differences between groups were analyzed using the Mann–Whitney U test at α = 0.05.Results: Protein adequacy was lower in the anemic group (74.4 ± 29.6%; mean rank 27.88) than in the non-anemic group (87.8 ± 23.9%; mean rank 37.13; p = 0.047; r = 0.248). Menstrual duration was longer in the anemic group (5.97 ± 1.28 days; mean rank 37.09) than in the non-anemic group (5.34 ± 1.06 days; mean rank 27.91; p = 0.040; r = 0.257). Both effect sizes were small.Conclusions: Adolescent girls with anemia had lower protein adequacy and longer menstrual duration than those without anemia. Nutrition education to support adequate protein intake and targeted hemoglobin monitoring may contribute to anemia prevention.